2021
DOI: 10.1371/journal.pone.0251290
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of intact extracellular vesicles from cryopreserved samples

Abstract: Extracellular vesicles (EVs) have emerged as promising candidates in biomarker discovery and diagnostics. Protected by the lipid bilayer, the molecular content of EVs in diverse biofluids are protected from RNases and proteases in the surrounding environment that may rapidly degrade targets of interests. Nonetheless, cryopreservation of EV-containing samples to -80°C may expose the lipid bilayer to physical and biological stressors which may result in cryoinjury and contribute to changes in EV yield, function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This condition of storage showed loss of EVs, changes in the lipid integrity of EVs morphology, loss of cargoes (such as RNA and protein), number of EVs were decreased on the other hand size range increased. The −80°C storage have other limitations such as high cost and transportation ( Tessier et al, 2021 ; Yuan et al, 2021 ). However, the most favorable condition for storage of isolated EVs is −80°C.…”
Section: Advantages and Disadvantages Of Cell-derived Nanovesicles Fo...mentioning
confidence: 99%
“…This condition of storage showed loss of EVs, changes in the lipid integrity of EVs morphology, loss of cargoes (such as RNA and protein), number of EVs were decreased on the other hand size range increased. The −80°C storage have other limitations such as high cost and transportation ( Tessier et al, 2021 ; Yuan et al, 2021 ). However, the most favorable condition for storage of isolated EVs is −80°C.…”
Section: Advantages and Disadvantages Of Cell-derived Nanovesicles Fo...mentioning
confidence: 99%
“…Preliminary evidence was also provided to show how EV HB‐Chip can be functionalized with ACE2 receptor for SARS‐Cov2 virus or cell‐specific Ab cocktail (CD3, CD4 or CD8 T‐cells) to capture virus or cell‐specific EVs from the plasma of COVID‐19 patients, and how these EVs can be used for RNAseq to potentially identify patients suitable for immunotherapy or diagnosis of COVID‐19 based on detection of viral RNA in EVs or plasma. Although the microfluidic systems seem to allow high purity isolation of EVs from small volume plasma samples, several areas for further research and development were identified by the expert panel, such as the need to combine with sophisticated hardware and software, select optimum Ab cocktails, address limitations associated with the usage of whole blood and investigate how haemolysis, activation of blood cells, coagulation during blood or plasma storage may affect the efficiency of EV isolation (Tessier et al., 2021 ; Wong et al., 2017 ).…”
Section: Lessons From Other Cell Membrane‐derived Vesicles and Other ...mentioning
confidence: 99%
“…EVs are currently being tested for their potential clinical application based on their biological origin, lower immunogenicity, versatility in engineering the membrane or cargo and their potential for tissue‐specific targeting (Anselmo & Mitragotri, 2021 ; Herrmann et al., 2021 ; Kalluri & LeBleu, 2020 ; Mentkowski et al., 2018 ; Murphy et al., 2019 ). However, limited knowledge of the heterogeneity of EV populations or their corresponding cargos, challenges in minimizing off‐target effects and improving tissue‐specific targeting, short half‐life and bioactivity in the circulation, selection of the dose (EVs vs. therapeutic cargo), dosage strategy (size of dose vs. frequency), route of administration (intravenous or intratracheal or intramyocardial), poorly understood pharmacokinetics or pharmacodynamics in vivo, unknowns related to the scale‐up of manufacturing for the pharmaceutical grade EVs, challenges in ensuring batch to batch reproducibility and loss of EV function during cryopreservation (Tessier et al., 2021 ) pose challenges in the translation of EVs for the therapy of HLBS diseases. Besides functional optimization of engineered EVs, the process would also need to match the milestones for cell‐derived products set by regulatory agencies, such as ensuring control, standardization and reproducibility of EV sources (parent cells used for EV production), and the methods used for EV production, including appropriate product test methods, to ensure the reproducibility of the therapeutic effects of engineered EVs.…”
Section: Future Challenges and Concluding Remarksmentioning
confidence: 99%
“…Another study reported that EV concentration decreased significantly in plasma stored at −80 °C for 10–12 days compared to freshly isolated plasma samples. However, no significant difference was observed in the average size of EVs between the samples [ 69 ]. Platelets were frozen and cryopreserved for 24 h at −80 °C in 5–6% dimethyl sulfoxide (DMSO).…”
Section: Biofluids and Extracellular Vesicles Characterization Under ...mentioning
confidence: 99%